The role of social media in the scientific communication of faculty members at Allameh Tabatabai University - Golnessa Galyani-Moghaddam; Mitra Samiei; Maryam Kamali-Sarvestani (مطالعات رسانه‌های نوین, 2018)
The present research study endeavors to define the role of social media in the scientific communication of faculty members at Allameh Tabatabai University. It uses an analytical survey method. To collect the necessary data, a questionnaire was developed in accordance with Kietzmanns social media model and Zuccala’s invisible college concept as applied to scientific communication. The Cronbach alpha coefficient was used to verify the validity of the questionnaire; its value was 0.91. The statistical population was 460 members of the university’s academic staff. From this population, 150 people were randomly selected. SPSS software was used for data analysis. The results showed that the social medium preferred by faculty members was Google Scholar. An analysis of relationships showed that faculty members interacted mostly with other specialists in the country, while they also followed other colleagues and specialists via social media. The formation of groups occurred mostly within the university. Regarding dialogue and conversation, e-mail was the most popular medium in communication. Faculty members were honest in their use of social media in their communication. Finally, trust, identity, and information sharing were found to be at a medium level in communication through social media.